Molecular cloning, expression profiling and functional analyses of a cDNA encoding isopentenyl diphosphate isomerase from Gossypium barbadense. Issue 2 (28th January 2009) - Wang, Yechun; Qiu, Chengxiang; Zhang, Fei; Guo, Binhui; Miao, Zhiqi; Sun, Xiaofen; Tang, Kexuan
Abstract : Gossypol, a type of plant defence sesquiterpenoid phytoalexin, is synthesized from the MEP (2C-methyl-D -erythritol 4-phosphate) and MVA (mevalonate) pathway in the isoprenoid biosynthetic system. The key step is the isomerization of IPP (isopentenyl diphosphate) to DMAPP (dimethylallyl diphosphate), which is catalysed by IPI (IPP isomerase; EC 5.3.3.2). A full-length cDNA encoding IPI (designated GbIPI ) was cloned from Gossypium barbadense by RACE (rapid amplification of cDNA ends). The full-length cDNA of GbIPI was 1205 bp and contained a 906 bp ORF (open reading frame) encoding a protein of 302 amino acids, with a predicted molecular mass of 34.39 kDa and an isoelectric point of 6.07. Amino acid sequence analysis revealed that the GbIPI has a high level of similarity to other IPIs. Southern-blot analysis revealed that GbIPI belongs to a small gene family. Expression analysis indicated that GbIPI expression is highest in stems, followed by leaves, and is lowest in roots, and that the expression of GbIPI could be induced by Verticillium dahliae Kleb, MeJA (methyl jasmonate) and SA (salicylic acid). The functional colour assay indicated that GbIPI could accelerate the accumulation of β-carotene in Escherichia coli transformants. The cloning and functional analysis of GbIPI will be useful in increasing understanding of the role of IPI in isoprenoid biosynthesis at the molecular level.